Factors that influence students join entrepreneurship: a case study in bachelor of administrative science (Hons) student at Universiti Teknologi MARA (UiTM) Kampus Bandaraya Melaka / Afiq Azwar Azman and Nor Azlina Sulaiman - Azman, Afiq Azwar; Sulaiman, Nor Azlina (Faculty of Administrative Science and Policy Studies, 2014)
The study seeks to determine the factors of entrepreneurship involvement in entrepreneurship. A sample of 181 respondents at UiTM Kampus Bandaraya Melaka had been selected for this study. The findings show that the independent variables or factors that support our hypothesis are family background and entrepreneurship programmes. It means that not all of these two factors determine their relationship with the factors of student’s involvement in entrepreneurship. Simple random sampling (SRS) is used to distribute the questionnaire to selected respondents. Based on this finding, the major factor that influences students to join entrepreneurship is family background. While another independent variable has a significant relationship to the factor of student’s interest in entrepreneurship. This is due to the result of correlation coefficient that has been used. In conclusion, family background and entrepreneurship programme contribute to the factors of students’ interest in entrepreneurship.